Advanced Intelligent Systems for Sustainable Development (AI2SD'2018) Vol 4: Advanced Intelligent Systems Applied to Health - Ezziyyani, Mostafa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers papers presented at the International Conference on Advanced Intelligent Systems for Sustainable Development (AI2SD-2018), which was held in Tangiers, Morocco on 12-14 July 2018. Highlighting the latest research and advances in the field of healthcare, it shares essential insights into the health sector, and is intended to stimulate further discussion and promote closer interdisciplinary collaboration among researchers and health professionals.
Keywords: Computational intelligence; Artificial intelligence; Medical informatics; Biomedical engineering; Computational Intelligence; Artificial Intelligence; Health Informatics; Biomedical Engineering and Bioengineering